The Rome Call and The Dynamics of Institutionalizing Ethics in Artificial Intelligence Governance - Pakpahan, Saiman; Ermansyah, Bambang Putra (Universitas Sultan Ageng Tirtayasa, 2025)
This article examines the institutionalization of ethical norms in the governance of artificial intelligence (AI), focusing on the Rome Call for AI Ethics as a global initiative. The study addresses the ethical challenges posed by AI, including algorithmic bias, privacy violations, and social inequality. Using constructivism and the